2020
DOI: 10.9734/arrb/2020/v35i530227
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Divergence in Corn Genotypes for High and Low Phosphorus in Pará, Brazil

Abstract: Aims: The objective of this study was to estimate the genetic divergence between ten corn genotypes in the 2017/18 crop, under high and low phosphorus. Study Design: The experimental design used in each test was randomized blocks, the treatments were: ten genotypes in two levels of phosphorus and three replications. Place and Duration of Study: Sítio Vitória, municipality of Santa Maria das Barreiras, state of Pará, Brazil, in the 2017/18 crop. Methodology: The experimental plot consisted of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
0
0
Order By: Relevance
“…The inbred lines utilized in this study did not form clusters according to their genetic background and origin, which means a high level of variation is present among and within different backgrounds. Cluster analysis had been carried out in various studies based on quantitative traits for the selection of LP-tolerant maize [35][36][37]. In this experiment, it was found that the data were normally distributed through boxplot analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The inbred lines utilized in this study did not form clusters according to their genetic background and origin, which means a high level of variation is present among and within different backgrounds. Cluster analysis had been carried out in various studies based on quantitative traits for the selection of LP-tolerant maize [35][36][37]. In this experiment, it was found that the data were normally distributed through boxplot analysis.…”
Section: Discussionmentioning
confidence: 99%